Altered Na+-K+ pump activity and plasma lipids in salt-hypertensive Dahl rats: relationship to Atp1a1 gene - Zicha, J; Negrin, C D; Dobesová, Z; Carr, F; Vokurková, M; McBride, M W; Kunes, J; Dominiczak, A F (Physiological genomics, 2001)
A genetic variant of the gene for the alpha(1)-isoform of Na(+)-K(+)-ATPase (Atp1a1) was suggested to be involved in the pathogenesis of salt hypertension in Dahl rats through altered Na(+):K(+) coupling ratio. We studied Na(+)-K(+) pump activity in erythrocytes of Dahl salt-sensitive (SS/Jr) rats in relation to plasma lipids and blood pressure (BP) and the linkage of polymorphic microsatellite marker D2Arb18 (located within intron 1 and exon 2 of Atp1a1 gene) with various phenotypes in 130 SS/Jr x SR/Jr F(2) rats. Salt-hypertensive SS/Jr rats had higher erythrocyte Na(+) content, enhanced ouabain-sensitive (OS) Na(+) and Rb(+) transport, and higher Na(+):Rb(+) coupling ratio of the Na(+)-K(+) pump. BP of F(2) hybrids correlated with erythrocyte Na(+) content, OS Na(+) extrusion, and OS Na(+):Rb(+) coupling ratio, but not with OS Rb(+) uptake. In F(2) hybrids there was a significant association indicating suggestive linkage (P < 0.005, LOD score 2.5) of an intragenic marker D2Arb18 with pulse pressure but not with mean arterial pressure or any parameter of Na(+)-K(+) pump activity (including its Na(+):Rb(+) coupling ratio). In contrast, plasma cholesterol, which was elevated in salt-hypertensive Dahl rats and which correlated with BP in F(2) hybrids, was also positively associated with OS Na(+) extrusion. The abnormal Na(+):K(+) stoichiometry of the Na(+)-K(+) pump is a consequence of elevated erythrocyte Na(+) content and suppressed OS Rb(+):K(+) exchange. In conclusion, abnormal cholesterol metabolism but not the Atp1a1 gene locus might represent an important factor for both high BP and altered Na(+)-K(+) pump function in salt-hypertensive Dahl rats.
Keywords: Rats; iontový transport; lipidy; krevní tlak; Hypertension; Sodium Chloride; Rats, Inbred Dahl; mužské pohlaví; sodíko-draslíková ATPasa; inhibitory enzymů; Cholesterol; polymorfismus genetický; ouabain; krysa rodu Rattus; Ouabain; Ion Transport; Lipids; Rubidium; Polymorphism, Genetic; Erythrocytes; potkani inbrední Dahl; erytrocyty; zvířata; Blood Pressure; rubidium; hypertenze; chlorid sodný; sodík; Sodium-Potassium-Exchanging ATPase; Sodium; Enzyme Inhibitors; Male; cholesterol; Animals